Estimation of the production cost of a kilogram of milk and its most influential variables - Calvo Hernández, Olga María (2021)
The objective of this study was to determine the production cost of one kilogram of milk and its most influential variables, at the Alfredo Volio Mata Experimental Station of the University of Costa Rica, for the period 2019-2020. The estimation of a production cost is a fundamental tool for decision-making within a production unit. Knowing its most influential components and variables allows each element to be evaluated individually, thus allowing a more focused analysis and approach to each of the parts that make it up and their influence on the total cost. For this, an ABC (Activity Based Costing) accumulation system was used, in which the main activities and sub-activities were defined and identified, as well as the needs for materials, supplies, labor, among others. From the above, a production cost of ₡ 713,04 ($ 1,16) per kilogram of milk was obtained. The cost is characterized by being highly influenced by food (46,52%), labor (23,38%) and dairy materials (8,97%); and to a lesser extent (less than 10%) due to variables such as pasture maintenance, eventual diseases, cleaning materials, water, electricity and reproductive management. The cost obtained at the Station is a reflection of its productive management and the investigative and non-profit purpose of this production unit.